2022
DOI: 10.1186/s40545-022-00438-8
|View full text |Cite
|
Sign up to set email alerts
|

Contributions and challenges of community pharmacists during the COVID-19 pandemic: a qualitative study

Abstract: Background Healthcare services across the world have been deeply impacted by the COVID-19 pandemic. In primary care, community pharmacists have had an important role in the frontline healthcare response to the pandemic. Objectives This study aimed to explore the experiences, contributions and perceived challenges of community pharmacists regarding the provision of healthcare services during the COVID-19 pandemic. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Qualitative research in France and a UK survey of pharmacy professionals who had pledged to be an Antibiotic Guardian found good knowledge of AMR and motivation to engage in AMS initiatives [ 26 , 27 , 28 ]. The Antibiotic Guardian survey found significant differences in knowledge of AMR depending on job roles, with pharmacists scoring higher and dispensing staff lower [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research in France and a UK survey of pharmacy professionals who had pledged to be an Antibiotic Guardian found good knowledge of AMR and motivation to engage in AMS initiatives [ 26 , 27 , 28 ]. The Antibiotic Guardian survey found significant differences in knowledge of AMR depending on job roles, with pharmacists scoring higher and dispensing staff lower [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings echo the previous evaluation of PAMSI in 2020 which found that pharmacy staff lacked time, resources and staffing to address AMS, and physical resources such as the TARGET Antibiotic Checklist were not feasible for patients who have their prescription delivered or picked up by representatives [ 10 ]. Issues of pharmacy staffing, time and resources have been highlighted in other literature [ 26 , 28 , 34 ]. The feedback survey suggests that most pharmacy teams were reading out the questions to patients rather than having them fill these in directly, as it was designed, which may take more time.…”
Section: Discussionmentioning
confidence: 99%
“…35 Furthermore, pharmaceutical associations should construct a system to actively and knowingly prepare, respond, and recover from disasters and emergencies, allowing more CPs to participate. 36 Pharmaceutical associations should allow the integration of CPs into a health-care team when responding to a local disaster or pandemic. This study used the PPRR phase to assess the importance and performance of CPs' roles in disaster management.…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacists significantly enabled a collective response to the pandemic and greatly saved a lot of people from the severity of the Covid-19 pandemic. The professionals managed an effective control of the pandemic by assuming novel roles in public health, such as being vaccinators, testers, screeners, and educators (Durand et al, 2022). Pharmacists in the communities also contributed to the control of the pandemic by ensuring the continuity of pharmaceutical services amidst the health risks presented by Covid-19.…”
Section: Literature Reviewmentioning
confidence: 99%